A Jurisprudential Analysis of in vitro fertilisation within the Framework of Islamic Law - Nasiri Nasiri (TARUNALAW Journal of Law and Syariah, 2026)
The vitro fertilisation is an interesting subject to study. There is a chance that the child from in vitro fertilisation will not be recognized by the parents if it is different from expectations. Therefore, in terms of recognition, both in terms of positive law and Islamic law, it is an interesting problem to study. The aims of this study are: (1) to find out Islamic law views in vitro fertilisation; (2) to find out the form of sanctions insemination of in vitro fertilisation according to Islamic law. The design used in this study was normative legal research with a (statute approach) from the perspective of Islamic law. In this study, documentation data collection techniques were used. Analysis technique normative legal research, usedwas descriptive-analysis with evaluation, interpretive, construction, and content analysis. Islamic criminal law views on donor sperm insemination is halal in Islamic perspective. The law is the same as adultery and children born from this kind of insemination have the same status as children born outside of a legal marriage. Perspective of Islamic criminal law on perpetrators. Artificial insemination with in vitro fertilisation is restricted as is the law of fornication in adultery, however, artificial insemination with in vitro fertilisation is ta'zir on the grounds that the elements in the had of adultery are not fulfilled because there is no direct sexual intercourse.